القيم الوطنية في شعر "في القدس" لتميم البرغوثي (الدراسة السيميائية لفرديناند دي سوسور) - Jakfar Shiddiq, Muhammad; hakim, Farid (Journal of Arabic Language and Literature (ALLAIS), 2022)
This study discusses the meaning and values ​​of nationalism contained in the poem "Fi al-Quds" by Tamim al-Borghouti with semiotic analysis of Ferdinand de Saussure. The purpose of this research is to find out the meaning contained in Tamim Al-Barghouti's poem "Fi al-Quds" and to identify the meaning of nationalism that is formed in Tamim Al-Barghouti's poem "Fi al-Quds". This research is a qualitative descriptive study with library methods, data sources from books and documents, data collection methods in the form of documentation methods and data validity in the form of triangulation methods, while data analysis includes data reduction, data presentation, conclusion drawing or verification. After that, the researcher reveals the intrinsics contained in the poem, then explains the signifiers and signifieds using Ferdinand de Saussure's semiotic theory, and finally determines the values ​​of nationalism which include the values ​​of love for the homeland, courage, self-sacrifice, and obedience.